Utilizando as planilhas eletrônicas para determinar os elementos das cônicas - Batista, Fernando do Carmo (2014)
In this paper, we will discuss general conic and quadratic equation, historical and theoretical part, applying this knowledge in designing spreadsheets to identify which conic (ellipse, parabola or hyperbola, as well as their degenerate cases) and determine its main elements from their equations in canonical or general high school.For better understanding and assessment of what will be, we will make use of interactive activities with the use of computer.